Caffeine, coffee and ephedrine: impact on exercise performance and metabolism - Graham, T. E. (Canadian Journal of Applied Physiology, 2001)
This paper addresses areas where there is controversy regarding caffeine as an ergogenic aid and also identifies topics that have not been adequately addressed. It is clear that caffeine, in moderate amounts, can be used orally as an ergogenic aid in aerobic activity lasting for more than 1 min. It increases endurance and speed, but not maximal VO2 and related parameters. While there are fewer well-controlled studies for resistance exercise, the literature would suggest similar improvements: increased endurance at submaximal tension and power generated in repeated contractions and no change in maximal ability to produce force. It is likely that theophylline (a related methylxanthine) has similar actions and it has been suggested that the combination of caffeine and sympathomimetics may be a more potent erogenic aid. The voids in our understanding of caffeine include the dose (what amount is optimal, what vehicle is used to deliver the drug as well as method, pattern, and mode of administration), the potential side effects (particularly in competitive settings), health implications (insulin resistance and if combined with ephedrine, cardiovascular risks) and mechanisms of action. It appears unlikely that increased fat oxidation and glycogen sparing is the prime ergogenic mechanism.